2000
DOI: 10.1177/109634800002400402
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Justice and Attributions Regarding Service Failure and Recovery on Post-Recovery Customer Satisfaction and Service Quality Attitudes

Abstract: This research examines the impact of attributions regarding service failure and recovery on the relationship between satisfaction and service quality by studying a service failure in the hospitality industry resulting from overbooking. In addition, the impact of perceived justice on satisfaction and service quality is analyzed. Finally, the ability of superior recovery to completely mitigate the dissatisfaction resulting from low-harm service failure is addressed. In doing so, the relationship between satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 53 publications
2
71
1
5
Order By: Relevance
“…Many authors have found that all three forms of justice including distributive justice, procedural justice, interactional justice have a positive effect on overall service recovery satisfaction (Patterson et al, 2006;dos Santos & Fernandes, 2008;Kim et al, 2009;Karande et al, 2007;Karatepe, 2006;Ok et al, 2005;Smith et al, 1999;Tax et al, 1998;Clemmer & Schneider, 1996;Kau & Loh, 2006). The effects of dimensions of justice on customers' recovery satisfaction have been studied in different service industries as well, including, hotel customers, (Karatepe 2006), mobile phone buyers (Kau & Loh 2006), Undergraduate students, hotel customers (Smith et al, 1999) and Airline passengers (McCollough et al, 2000). Thus, based on the above discussion, this study proposed the following hypotheses:…”
Section: Perceived Justice and Recovery Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have found that all three forms of justice including distributive justice, procedural justice, interactional justice have a positive effect on overall service recovery satisfaction (Patterson et al, 2006;dos Santos & Fernandes, 2008;Kim et al, 2009;Karande et al, 2007;Karatepe, 2006;Ok et al, 2005;Smith et al, 1999;Tax et al, 1998;Clemmer & Schneider, 1996;Kau & Loh, 2006). The effects of dimensions of justice on customers' recovery satisfaction have been studied in different service industries as well, including, hotel customers, (Karatepe 2006), mobile phone buyers (Kau & Loh 2006), Undergraduate students, hotel customers (Smith et al, 1999) and Airline passengers (McCollough et al, 2000). Thus, based on the above discussion, this study proposed the following hypotheses:…”
Section: Perceived Justice and Recovery Satisfactionmentioning
confidence: 99%
“…As it was mentioned in the introduction section, past studies have examined the effect of perceived justice on recovery satisfaction (Karatepe, 2006;Kau & Loh 2006;Smith et al, 1999;McCollough et al, 2000). However, the degrees of the relationship between perceived justice and recovery satisfaction might not be the same across corporate image levels.…”
Section: Perceived Justice Recovery Satisfaction and Brand Imagementioning
confidence: 99%
“…A superior recovery is examined to be critical to repurchase intentions, post-recovery satisfaction and customer retention [15][16] [18]. Taking Hampton Inn hotels in the USA as a practical example, approximately $11 million extra revenue has been derived from the maintaining of service guarantee and retaining customers [10].…”
Section: Service Failure and Recoverymentioning
confidence: 99%
“…responding to service failure). [18] demonstrated that the better performance of service recovery, the higher level of customer satisfaction. Consequently, it is imperative to recover service failure to reduce risks of financial loss and create long-term customer loyalty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation